Family-Oriented School Culture for Student Well-Being in Indonesian Islamic Junior High Schools: Advancing Sustainable Development Goal 4 - Zuhrotul Mufidah; Erny Roesminingsih; Karwanto Karwanto (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: Student well-being has become an increasingly important indicator of educational quality; however, existing research has largely examined it through individual programmes or psychological interventions rather than as a product of school culture. This article investigates how Family-Oriented School Culture fosters student well-being in Islamic junior high schools. Method: A qualitative multisite case study was conducted in two Islamic junior high schools in Sidoarjo, Indonesia, using in-depth interviews, participant observation, and document analysis. Data were analysed through within-site and cross-site analysis, with triangulation employed to enhance credibility. Result: Analysis identified four interconnected dimensions of Family-Oriented School Culture: (1) a family-like school climate, (2) emotional and spiritual support, (3) collective character development, and (4) non-academic support systems. Together, these dimensions formed an integrated organizational culture that strengthened students' sense of belonging, emotional security, responsibility, empathy, discipline, and interpersonal relationships. Positive character and well-being developed simultaneously through sustained interactions among teachers, students, families, and the wider school community rather than through isolated support programmes. Novelty: By conceptualizing Family-Oriented School Culture as an organizational mechanism for student well-being, the article extends existing literature that primarily emphasizes individual interventions and school climate as separate constructs. The proposed framework offers practical guidance for school leaders in developing safe, inclusive, supportive, and family-oriented educational environments that contribute to student well-being and the achievement of Sustainable Development Goal 4.